2010
DOI: 10.1186/1748-5908-5-62
|View full text |Cite
|
Sign up to set email alerts
|

Embedding effective depression care: using theory for primary care organisational and systems change

Abstract: BackgroundDepression and related disorders represent a significant part of general practitioners (GPs) daily work. Implementing the evidence about what works for depression care into routine practice presents a challenge for researchers and service designers. The emerging consensus is that the transfer of efficacious interventions into routine practice is strongly linked to how well the interventions are based upon theory and take into account the contextual factors of the setting into which they are to be tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 28 publications
4
70
0
Order By: Relevance
“…Background Gunn et al 62 reported that GPs perceive patient engagement to be of fundamental importance in dealing with depression. Older people may be reluctant to define their distress as a mental health problem, with implications for treatment acceptance.…”
Section: Chapter 7 Qualitative Findingsmentioning
confidence: 99%
“…Background Gunn et al 62 reported that GPs perceive patient engagement to be of fundamental importance in dealing with depression. Older people may be reluctant to define their distress as a mental health problem, with implications for treatment acceptance.…”
Section: Chapter 7 Qualitative Findingsmentioning
confidence: 99%
“…35 In previous studies, the measure of observed patient centredness used in the present study (the MPCC) has been linked to patient satisfaction, 27 reduced diagnostic testing, 18 and improved patient health status. 19 There is substantial evidence of the beneficial effects of practitioner empathy on the outcomes of consultations with patients with mental health problems.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…376 Improvement of primary care 'quality' and organisational change are both important. 377 Any initiative needs to be seen as relevant to practices' everyday work, and flexible enough to respond to the challenges posed by the needs of an individual practice. 378 As we explained in Chapter 2, the AMP programme assimilated evidence on the nature of access problems for underserved groups, and views of how access might be more equitable.…”
Section: Amp Trainingplusmentioning
confidence: 99%
“…We used evidence gained from phase 2, together with our knowledge of and experience in the diffusion of innovation 377,399,400 to inform implementation strategies at three complementary levels:…”
Section: Introductionmentioning
confidence: 99%